Synergistic impact of photocatalyst and dopants on pharmaceutical-polluted waste water treatment: a review. Issue 1 (1st January 2021) - Shukla, Shraddha; Pandey, Himanshu; Singh, Prashansha; Tiwari, Anish Kumar; Baranwal, Vikas; Pandey, Avinash C
ABSTRACT: In last few decades, pharmaceutical waste management emerged as one of major environmental concern. These contaminants have shown their severe impact on living being. Several methods for their treatment such as UV degradation, nano-filtration, reverse osmosis and Photocatalysis are being used. Photocatalysis is a favourable and environmentally safe method for remediation of organic pollutants. Photocatalytic oxidation process involves destruction of the organic pollutants in presence of an oxidizing agent like oxygen, light source and the semiconductor photocatalyst. Metal oxides have shown greater capability towards treatment of Pharamaceutically Active Compounds (PhACs). In present review, authors have discussed about diverse metal oxides (TiO2, ZnO, CuO, Fe2 O3, Ag2 O, WO3, Bi2 O3 and Pt), their physical and chemical properties and unique ability to recycle waste water, mechanism of action, applications and their efficiencies along with possible solutions to make them more efficient. Metal oxides do have limitations like faster recombination rate, lower ability for the full usage of light and lesser migration of photo-generated electrons. Therefore, different doping materials, those are metals, non-metals and metalloids can be applied for improving their performances is suggested. In nutshell, it can be concluded that doped metal oxides can be used as potential tools for the treatment of organic pollutants.